Delivery cost of the first public sector introduction of typhoid conjugate vaccine in Navi Mumbai, India. - Dayoung Song; Sarah W Pallas; Rahul Shimpi; N Ramaswamy; Pradeep Haldar; Pauline Harvey; Pankaj Bhatnagar; Arun Katkar; Niniya Jayaprasad; Abhishek Kunwar; Sunil Bahl; Win Morgan; et al. (PLOS Global Public Health, 2023)
Navi Mumbai Municipal Corporation (NMMC), a local government in Mumbai, India, implemented the first public sector TCV campaign in 2018. This study estimated the delivery costs of this TCV campaign using a Microsoft Excel-based tool based on a micro-costing approach from the government (NMMC) perspective. The campaign's financial (direct expenditures) and economic costs (financial costs plus the monetized value of additional donated or existing items) incremental to the existing immunization program were collected. The data collection methods involved consultations with NMMC staff, reviews of financial and programmatic records of NMMC and the World Health Organization (WHO), and interviews with the health staff of sampled urban health posts (UHPs). Three UHPs were purposively sampled, representing the three dominant residence types in the catchment area: high-rise, slum, and mixed (high-rise and slum) areas. The high-rise area UHP had lower vaccination coverage (47%) compared with the mixed area (71%) and slum area UHPs (76%). The financial cost of vaccine and vaccination supplies (syringes, safety boxes) was $1.87 per dose, and the economic cost was $2.96 per dose in 2018 US dollars. Excluding the vaccine and vaccination supplies cost, the financial delivery cost across the 3 UHPs ranged from $0.37 to $0.53 per dose, and the economic delivery cost ranged from $1.37 to $3.98 per dose, with the highest delivery costs per dose in the high-rise areas. Across all 11 UHPs included in the campaign, the weighted average financial delivery cost was $0.38 per dose, and the economic delivery cost was $1.49 per dose. WHO has recommended the programmatic use of TCV in typhoid-endemic countries, and Gavi has included TCV in its vaccine portfolio. This first costing study of large-scale TCV introduction within a public sector immunization program provides empirical evidence for policymakers, stakeholders, and future vaccine campaign planning.